A new trend in Sabancı University Information Center: QR Code Application - Özel, Cem; Akkurt, Mine (Qualitative and Quantitative Methods in Libraries; Vol 4 No 1 (2015): March 2015 Issue, 2017)
The rapid development of mobile technologies in recent years has facilitated the use of the popular QR code application for various purposes. The new generation‟s rapid adaptation to change has allowed this application's widespread usage. QR codes with structural properties can be supported with new ideas. It has developed into a new trend in libraries/information centers, as well as in the other areas. One of the usage areas of the QR code is in the marketing field. In this study, various QR code applications used for study room booking, filling out request forms, promoting e-resources and especially e-books which are successfully being practiced in Sabancı University Information Center will be emphasized.